Salmonella group D septicemia and meningitis in pediatric HIV patient with COVID-19 pneumonia : A fetal case - Pacharatanasarn, Onsiree (Royal Thai Air Force Medical Gazette, 2022)
Objective: Viral and bacterial have been associated with increased morbidity and mortality among patients with HIV. We report co-infection of COVID-19 and salmonella in fetal case. Method : A 10-year-old boy was diagnosed with HIV infection. He presented with fever. In 2 day ago, he presented with diarrhea and drownsiness. The test was found rt PCR SARCOV2 positive. Blood culture and csf culture found salmonella group D : A fetal case Conclusion : Salmonella is bacterial was cause of severe in HIV patient so we should concern about the patients who is present with diarrhea . And COVID-19 is viral that co-infection with other bacterial